Connectivity Index of Generalized Uncertain Graph. (23rd May 2022) - Wang, Jinchan; Gao, Xiulian; Zhou, Xiaoshuang; Guo, Changyou; Yin, Xiuling
Abstract : In the application of classical graph theory, there always are various indeterministic factors. This study studies the indeterministic factors in the connected graph by employing the uncertainty theory. First, this study puts forward two concepts: generalized uncertain graph and its connectivity index. Second, it presents a new algorithm to compute the connectivity index of an uncertain graph and generalized uncertain graph and verify this algorithm with typical examples. In addition, it proposes the definition and algorithm of α -connectivity index of generalized uncertain graph and verifies the stability and efficiency of this new algorithm by employing numerical experiments.